THE PHENOMENON OF K-DRAMA (KOREAN WAVE) IN INFLUENCING THE LEVEL OF FINANCIAL LITERACY AND PUBLIC FINANCIAL INCLUSION - Islamiah Kamil; Hendi Prihanto (Universitas prof. Dr. Moestopo (Beragama), 2022)
The purpose of this study was to determine the effect of K-Drama (Korean Wave) on Community Financial Literacy During the Covid-19 Pandemic and to determine the effect of K-Drama (Korean Wave) on Public Financial Inclusion During the Covid-19 Pandemic in the Jakarta and Tangerang Areas. . The analysis technique used is simple linear regression. Hypothesis testing to determine the effect of independent variables on the dependent variable as a whole is by using partial hypothesis testing carried out by t-test. The final result of this study is that K-Drama (Korean Wave) has a significant effect on Community Financial Literacy during the Covid-19 Pandemic in the Jakarta and Tangerang Regions. And K-Drama (Korean Wave) has a significant effect on Public Financial Inclusion During the Covid-19 Pandemic in the Jakarta and Tangerang Areas